Cardiac Arrhythmias Translational Approach from Pathophysiology to Advanced Care - Zima, Endre (IntechOpen, 2022)
Cardiac arrhythmias are common triggers of emergency admission to cardiology or high-dependency departments. Most cases are easy to diagnose and treat, while others may present a challenge to healthcare professionals. A translational approach to arrhythmias links molecular and cellular scientific research with clinical diagnostics and therapeutic methods, which may include both pharmacological and non-pharmacologic treatments. This book presents a comprehensive overview of specific cardiac arrhythmias and discusses translational approaches to their diagnosis and treatment.